Pro Clean Sdn. Bhd.: shredding dustbin / Muhammad Hadziq Mohd Narang ...[et al.] - Mohd Narang, Muhammad Hadziq; Muhamad Jamil, Muhammad Farris; Mohd Saufi, Muhammad Safri Azmi; Mohd Asari, Mohd Kaizal; Mahasan, Mohamad Huzaifar; Mohd Saleh, Muhammad Taufiq (2016)
As for the business we are selling a dustbin for everyday used. As we go through with the changes of environment and modernization, most people nowadays tend to produce more waste products and have nowhere to store it.